Dugem Halal: Fenomena dan Reaksi Netizen Pada Akun @alfiyatunnuroh - Hartono, Toni; Harahap, Helmawati; Apriyani Jemmi, Aulia; Ananda Tasya, Sandrina; Pratama, M. Aditya (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2025)
This study aims to examine the strategy of empathetic da’wah communication implemented by female preachers in fostering spiritual and emotional relationships with mosque congregants. The research focuses on the experience of Ustadzah Sri Maryatun, a senior female preacher at Nurul Iman Mosque in Jakarta. The method employed is descriptive qualitative research, using in-depth interviews and literature review as data collection techniques. The findings reveal that empathetic communication—manifested through personal engagement, non-judgmental listening, and appreciation of the mad’u’s life struggles—is key to the success of community-based da’wah. The female preacher in this study functions not only as a religious messenger but also as a companion and familial figure to her congregants. Moreover, her spiritual resilience in facing internal family pressure reinforces her dedication to da’wah. This study also presents a fresh perspective on gender-based da’wah communication grounded in humanistic values.